2021
DOI: 10.3389/fchem.2021.715052
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Activation of Synthetic Aluminosilicate Glass With Basaltic Composition

Abstract: Alkali-activated materials (AAMs) are a potential alternative to Portland cement because they can have high strength, good durability and low environmental impact. This paper reports on the structural and mechanical characteristics of aluminosilicate glass with basalt-like compositions, as a feedstock for AAMs. The alkali-activation kinetics, microstructure, and mechanical performance of the alkali activated glass were investigated. The results show that AAMs prepared from basalt glass have high compressive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…One of the most promising alternatives is alkali-activated materials (AAM) ( Rivera et al, 2021 ; van Deventer et al, 2021 ), also referred to as geopolymers. The terms geopolymers ( Davidovits, 1989 ), inorganic polymers ( Van Wazer, 1970 ), alkali-activated cement ( Palomo and López de la Fuente, 2003 ), and geocement ( Krivenko, 1994 ) are all used to describe these binding materials, which can provide comparable, or higher performance than the traditional cementitious binders ( Wang et al, 2019 ; Alzeer et al, 2021 ) with significantly lower greenhouse emissions ( Gartner, 2004 ; Palomo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising alternatives is alkali-activated materials (AAM) ( Rivera et al, 2021 ; van Deventer et al, 2021 ), also referred to as geopolymers. The terms geopolymers ( Davidovits, 1989 ), inorganic polymers ( Van Wazer, 1970 ), alkali-activated cement ( Palomo and López de la Fuente, 2003 ), and geocement ( Krivenko, 1994 ) are all used to describe these binding materials, which can provide comparable, or higher performance than the traditional cementitious binders ( Wang et al, 2019 ; Alzeer et al, 2021 ) with significantly lower greenhouse emissions ( Gartner, 2004 ; Palomo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The glass could also be prepared from combinations of abundant silicate minerals such as anorthite, olivine and wollastonite [37] and therefore, it has potential for large-scale production and utilization with low raw-material related CO 2 emissions as compared to PC. The synthesis of the glass presented in this study and its performance as alkali activated materials (AAMs) has recently been reported [38]. In this work, we investigated the hydration kinetics, hydration phases, pozzolanic reactivity and mechanical properties of blended cements containing the developed glass and compared their SCM performance to commonly applied GBFS.…”
Section: Introductionmentioning
confidence: 99%